Influence of impurity on electronic transition in coherent-strained quantum dot - Dan'kiv, O.O.; Peleshchak, R.M. (Functional Materials, 2006)
The influence of impurity on energy breadth of an optical gap for quantum dot is studied within the framework of deformation potential model. It is established that with size increase of a quantum dot with an ionization donor dopant an optical gap diminishes.
For smaller radiuses (R₀ ~ 40 Å ÷ 57 Å) energy breadth of the basic optical transition Е in quantum dots with donor dopants is greater, than in unblended ones. For the major sizes of quantum dots R₀ ≥ 58 Å the converse effect is observed. В рамках модели деформационного потенциала исследовано влияние примеси на энергетическую ширину оптической щели квантовой точки. Установлено, что с увеличением размеров квантовой точки с ионизированной донорной примесью оптическая щель суживается. Для меньших радиусов (R₀ ~ 40 Å ÷ 57 Å) энергетическая ширина основного оптического перехода Е в квантовых точках с донорными примесями больше, чем без примесей. При больших размерах квантовых точек R₀ ≥ 58 Å наблюдается обратный эффект. У рамках моделi деформацiйного потенцiалу дослiджено вплив домiшки на енергетичну ширину оптичної щiлини квантової точки. Встановлено, що зi збiльшенням розмiрiв квантової точки з iонiзованою донорною домiшкою оптична щiлина звужується. Для менших радiусiв (R₀ ~ 40 Å ÷ 57 Å) енергетична ширина основного оптичного переходу Е у квантових точках з донорними домiшками бiльша, нiж без домiшок. У разi бiльших розмiрiв квантових точок R₀ ≥ 58 Å спостерiгається протилежний ефект.